2007
DOI: 10.1111/j.1348-0421.2007.tb04001.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of All RND‐Type Efflux Transporters in Vibrio cholerae Non‐O1

Abstract: Resistance Nodulation cell Division (RND) efflux transporters are thought to be involved in mediating multidrug resistance in Gram‐negative bacteria, including Vibrio cholerae non‐O1. There are six operons for putative RND‐type efflux transporters present in the chromosome of V. cholerae O1 including two operons, vexAB and vexCD, which had already been identified. All of the six operons were cloned from V. cholerae non‐O1, NCTC4716 by the PCR method, introduced, and expressed in cells of drug hypersusceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…Supporting this notion is the recent report showing that expression of the vexGH and vexIJK RND efflux systems may be induced in vivo in humans (31). In addition, Rahman et al recently reported that V. cholerae vexEF can produce a functional multiple-drug efflux system when recombinantly expressed in E. coli (51). Thus, it appears likely that the VexEF, VexGH, and VexLM RND efflux systems are produced under yet unknown conditions.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Supporting this notion is the recent report showing that expression of the vexGH and vexIJK RND efflux systems may be induced in vivo in humans (31). In addition, Rahman et al recently reported that V. cholerae vexEF can produce a functional multiple-drug efflux system when recombinantly expressed in E. coli (51). Thus, it appears likely that the VexEF, VexGH, and VexLM RND efflux systems are produced under yet unknown conditions.…”
Section: Discussionsupporting
confidence: 55%
“…Ongoing work in our laboratory is focused on determining whether VexEF functions in this respect. Lastly, vexGH, vexIJK, and vexLM did not produce functional efflux systems when expressed in E. coli (51). Our results showed that the VexIJK efflux system functions in SDS and Triton X-100 resistance in V. cholerae.…”
Section: Discussionmentioning
confidence: 75%
“…E. coli KAM32 (⌬acrB ⌬ydhE hsd⌬5), which lacks the major multidrug efflux pumps AcrAB and YdhE, is hypersusceptible to many antimicrobial agents (7). E. coli KAM42 (⌬acrB ⌬ydhE hsd⌬5 ⌬tolC), a tolC-deficient strain derived from KAM32, was constructed as described previously (32). Cells were grown in Luria (L) broth (18) at 37°C under aerobic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The V. cholerae genome contains 6 RND transporters (VexAB, VexCD/BreAB, VexEF, VexGH, VexIJK, and VexLM), and most of them require TolC for drug efflux (340)(341)(342)(343)(344)(345). VexAB seems to play a predominant role in the efflux of antibiotics (benzylpenicillin, erythromycin, and polymyxin B) and detergents (cholate, SDS, and Triton X-100) (341), although among the 6 RND systems cloned from a non-O1 strain, VexEF conferred the strongest resistance to an E. coli host (343). VexCD (confusingly "renamed" BreAB) is involved in bile efflux (340) and is induced by bile (342).…”
Section: Vibrio Sppmentioning
confidence: 99%